Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2016)
A dataset containing 364683 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Polypodiopsida", "HasCoordinate is TRUE", "BasisOfRecord is Specimen", "HasGeospatialIssue is FALSE", "DecimalLatitude is greater than or equal to -22", "DecimalLatitude is less than or equal to 9" ] } The dataset includes 364683 records from 200 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0005341-160509122628363/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences